THE RELATIONSHIP BETWEEN SELF-EFFICACY AND POSITIVE THINKING WITH PUBLIC SPEAKING ANXIETY IN STUDENTS - Octavianti Yogasuria, Chika; Faslah, Roni; Yohana, Corry (Jurnal Ilmu Psikologi dan Kesehatan (SIKONTAN), 2023)
The current study focused on examining the relationship between public speaking anxiety with self-efficacy and positive thinking among 100 students of SMK Negeri 48 Jakarta. Proportional random sampling was used in selecting the research participants and conducting the survey stage with a quantitative approach. The quantitative test used a correlational approach followed by multiple regression analysis. The application of the Likert scale is useful as a measuring scale in collecting research data related to the variables tested. The results of statistical tests using the Pearson Correlation Product Moment approach show that there is a significant negative relationship between self-efficacy and public speaking anxiety, the higher of self-efficacy can lower the level of public speaking anxiety, and or vice versa. The correlation test also shows that there is a negative correlation between positive thinking and public speaking anxiety. The results of multiple regression tests also show that self-efficacy and positive thinking together influence public speaking anxiety. This finding gives an effective contribution of 29.3%. The implications of these findings can be the basis and input related to the need for positive thinking training and increasing self-efficacy in students.